Non-porous hybrid coated polymer particles

By using nonporous polymer particle cores with silyl-modified surfaces and nonporous composite particles of nonporous organic-inorganic hybrid materials, the problem of stability and low separation efficiency of large biomolecules under high pH conditions is solved, and high efficiency and stable chromatographic separation is achieved.

CN119744199APending Publication Date: 2025-04-01WATERS TECHNOLOGY CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380061252.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-26
Filing Date
2023-02-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing chromatographic separation technology has problems of particle corrosion and low separation efficiency of large biomolecules under high pH conditions, making it difficult to maintain stability and obtain high resolution.

Method used

The nonporous polymer particle core with a silyl-modified surface is used, and nonporous organic-inorganic hybrid materials are provided on its surface to form stable nonporous composite particles to maintain stability under high pH conditions and improve the separation efficiency of large biomolecules.

Benefits of technology

The chromatographic separation maintained stable under high pH conditions is achieved, which improves the high resolution separation of large biomolecules, extends the retention time, and improves peak shape and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005280784040000181
    Figure BDA0005280784040000181
  • Figure BDA0005280784040000191
    Figure BDA0005280784040000191
  • Figure BDA0005280784040000201
    Figure BDA0005280784040000201
Patent Text Reader

Abstract

The present disclosure relates to non-porous composite particles that are non-porous polymer-based organic-inorganic materials. In various embodiments, the non-porous polymer core is surface-modified. In various embodiments, a non-porous organic-inorganic hybrid material is disposed on the modified surface of the core. The present disclosure relates to chromatographic separation devices comprising such non-porous composite particles.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of U.S. Provisional Application Serial No. 63 / 401,497, entitled “Non-Porous Hybrid Coated Polymer Particles,” filed on August 26, 2022. The entirety of the aforementioned application is incorporated herein by reference. Technical Field

[0003] The present technology relates to chromatographic materials. More specifically, the present technology relates to nonporous composite particles for chromatographic separations. Typically, the nonporous composite particles include a nonporous polymer core and a nonporous organic-inorganic hybrid material disposed around the core. Background Art

[0004] Chromatography is a separation method involving two phases, one being the stationary phase and the other being the mobile phase. Typically, the stationary phase is porous or non-porous particles packed into a column. The mobile phase flows through the packed column. The sample or analyte to be separated is injected at the beginning of the column and is transported through the system by the mobile phase. As they pass through the column, the different components of the sample are distributed according to their relative affinities for the two phases. The results of the chromatographic separation are then depicted via a chromatogram, where the sample components can be identified by the various peaks or patterns in the chromatogram.

[0005] Measuring the degree of separation between two components is often referred to as the resolution of each component. Resolution can be determined by the efficiency, selectivity, and retention of the separation process. Efficiency refers to the quality of separation of the sample components and is usually determined by the number of separable peaks in the chromatogram. Selectivity refers to the ability of the chromatography to separate the sample components and is usually measured by the retention ratio of the two peaks in question in the chromatogram and can be visualized as the distance between the apexes of the two peaks. Retention or retention time refers to the time it takes for a sample to pass through the chromatographic column and is usually measured as the time interval between the injection of the sample and the detection of its components on the chromatogram.

[0006] Adjusting the mobile phase pH is a powerful tool to improve the retention and selectivity of analytes, especially ionizable analytes, in chromatographic separations. In reversed-phase chromatographic separations of basic compounds, peptides, and biological samples, high pH mobile phases combined with high temperatures are often used to obtain extended retention, excellent peak shape, and good efficiency. Silica-based stationary phases have been preferred in the past due to their stability at neutral pH and high temperatures. However, a common disadvantage is that silica-based stationary phases are unstable at high pH due to dissolution-induced particle corrosion, which in turn limits its use in these applications. An alternative to silica-based stationary phases is to use polymer-based stationary materials. Polymer-based stationary particles have shown some promise, but also have some limitations in the choice of the desired surface chemistry.

[0007] Mass transfer and lateral diffusion properties are important in large biomolecules (e.g., those with a hydrodynamic radius greater than Some even exceed The high resolution separation of large biomolecules (those of large biomolecules) is extremely important. However, in the separation of large biomolecules, the diffusion path that the analyte must traverse between the nonporous stationary phase and the mobile phase is very short, and the column efficiency becomes independent of the flow rate. Therefore, there is a need for nonporous particles with hybrid compositions for the stationary phase that have the ability to remain stable at high pH and to obtain high resolution separations of large biomolecules. Summary of the invention

[0008] The present technology relates to non-porous composite particles for chromatographic separations. In particular, embodiments of the present technology relate to chromatographic separations of large biomolecules.

[0009] The technology disclosed herein includes a surface-modified nonporous polymer core and a nonporous organic-inorganic hybrid material disposed around the surface-modified nonporous polymer core. That is, embodiments of the present disclosure relate to a nonporous composite particle, which includes a nonporous polymer particle core with a modified surface and a nonporous organic-inorganic hybrid layer in contact with the modified surface. In some embodiments, the modified surface is a silyl-modified surface including a first functional group and a second functional group. In certain embodiments, the modified surface is covalently bonded and / or electrostatically bonded to the nonporous organic-inorganic hybrid material. Due to the use of such nonporous particles in the stationary phase of chromatographic separation, the nonporous particles can remain stable at high pH and obtain high resolution separation of large biomolecules.

[0010] In one aspect, the present technology is directed to a nonporous composite particle comprising a nonporous polymer particle core having a silyl-modified surface and a nonporous organic-inorganic hybrid layer in contact with the silyl-modified surface.

[0011] The above aspects may include one or more of the following features. In some embodiments, the nonporous polymer particle core of the nonporous composite particle is the product of at least one monomer. In some embodiments, at least one monomer is a free radical polymerizable monomer. In some embodiments, at least one monomer includes at least two functional groups. In some embodiments, at least one monomer is capable of being polymerized by ring-opening polymerization or polycondensation.

[0012] Some embodiments may include one or more of the following features (in combination with any of the above features). In some embodiments, the nonporous polymer core is divinylbenzene (80%). In some embodiments, the silyl-modified surface of the nonporous polymer particle core includes a first functional group and a second functional group, the first functional group includes a reactive silane, and the second functional group includes an organic polymerizable group. In some embodiments, the reactive silane includes an alkoxy group. In some embodiments, the organic polymerizable group includes a vinyl group. In some embodiments, the silyl-modified surface of the nonporous polymer particle is modified with at least one of N-vinylpyrrolidone, N-vinylcaprolactam, N,N-dimethylvinylbenzylamine, methacryloxypropyltrimethoxysilane, or p-phenylvinyltrimethoxysilane. In some embodiments, the silyl-modified surface of the nonporous polymer particle core includes at least one functional group covalently bonded to an organometallic compound. In some embodiments, the silyl-modified surface of the nonporous polymer particle core includes at least one functional group that electrostatically interacts with a nonporous organic-inorganic hybrid layer.

[0013] The additional features of the above aspects may include one or more features in the following features. In some embodiments, the thickness range of the nonporous organic-inorganic hybrid layer of the nonporous composite particles is 1nm to 4 microns, more preferably 25nm to 200nm. In some embodiments, the nonporous organic-inorganic hybrid layer has a pore volume less than 0.10cc / g. In some embodiments, the nonporous organic-inorganic hybrid layer comprises a material selected from the group consisting of the following: silica, aluminum oxide, titanium, cerium, zirconium, silicon dioxide, aluminum oxide, cerium oxide, zirconium oxide, ceramic materials and combinations thereof. In some embodiments, the nonporous organic-inorganic hybrid layer comprises a silicon-based material. In some embodiments, the silicon-based material comprises a silicon atom with one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the nonporous organic-inorganic hybrid layer comprises a substituted or unsubstituted alkylene, alkenylene, alkynylene or arylene moiety bridging two or more silicon atoms.

[0014] The present technology provides multiple advantages over current chromatographic separation methods. For example, the use of the nonporous composite particles described herein can provide high resolution separations of large biomolecules. That is, a nonporous polymer particle core having a silyl-modified surface and a nonporous organic-inorganic hybrid layer in contact with the silyl-modified surface can provide better separations of large biomolecules than the methods currently used in the industry. The present technology can remain stable at high pH. Therefore, in the large analyte separation of large biomolecules, chromatographic separations using the nonporous composite particles described herein can result in extended retention, better peak shape, and higher efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0015]

[0008] The foregoing features and advantages and other features and advantages provided by the present technology will be fully understood from the following description of exemplary embodiments when read in conjunction with the accompanying drawings.

[0016] Those skilled in the art will appreciate that the drawings are primarily for illustrative purposes and are not intended to limit the scope of the inventive subject matter described herein. The drawings are not necessarily drawn to scale; in some cases, various aspects of the inventive subject matter disclosed herein may be exaggerated or enlarged in the drawings to facilitate understanding of different features. In the drawings, the same reference numerals generally represent the same features (e.g., functionally similar and / or structurally similar elements).

[0017] Figure 1 is a schematic cross-sectional view of a nonporous composite particle according to an embodiment of the present disclosure.

[0018] Figure 2 The relationship between volume and particle diameter is illustrated for Example 2 according to the present disclosure.

[0019] Figure 3 is a scanning electron micrograph of a particle cross-section of an intact particle formed according to Sample 2C of the present disclosure.

[0020] Figure 4 is a scanning electron micrograph of intact particles formed according to sample 4G.

[0021] Figure 5 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 4G.

[0022] Figure 6 is a scanning electron micrograph of intact particles formed according to sample 4H.

[0023] Figure 7 is a scanning electron micrograph of a particle cross section of a complete particle formed according to sample 4H.

[0024] Figure 8 is a scanning electron micrograph of intact particles formed according to sample 4I.

[0025] Fig. 9 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 4I.

[0026] Fig.10 is a scanning electron microscope photograph of intact particles made according to Example 3 of the present disclosure.

[0027] Fig.11 is a magnified scanning electron microscope photograph of intact particles made according to Example 3 of the present disclosure.

[0028] Fig.12is a scanning electron micrograph of intact particles formed according to Sample 4G of the present disclosure and subsequently primed with poly(N-vinylpyrrolidone).

[0029] Fig.13 is a magnified scanning electron micrograph of an intact particle formed according to Sample 4H of the present disclosure and subsequently primed with poly(N-vinylpyrrolidone).

[0030] Fig.14 is a scanning electron micrograph of a particle cross section of a complete particle formed according to Sample 6D.

[0031] Fig.15 is a scanning electron micrograph of a particle cross section of a complete particle formed according to sample 6H. DETAILED DESCRIPTION

[0032] The present disclosure relates to non-porous composite particles, which include a non-porous polymer particle core with a silyl-modified surface and a non-porous organic-inorganic hybrid material in contact with the silyl-modified surface. That is, embodiments of the present disclosure relate to a non-porous composite particle, which includes a non-porous polymer (e.g., organic material) particle core with a modified surface and an organic-inorganic hybrid non-porous material (e.g., layer) in contact with the modified surface. In some embodiments, the modified surface is a silyl-modified surface comprising a first functional group (i.e., a reactive silane) and a second functional group (i.e., an organic polymerizable group). In certain embodiments, the modified surface is covalently bonded and / or electrostatically bonded to the organic-inorganic hybrid non-porous material.

[0033] like Figure 1 As shown, a nonporous composite particle 100 according to an embodiment of the present disclosure is provided. The nonporous composite particle 100 has a nonporous polymer particle core 110 and an organic-inorganic hybrid nonporous material 130 surrounding the core 110. In this embodiment, the nonporous polymer particle core 110 has a modified surface 120, and the organic-inorganic hybrid nonporous material 130 is disposed on the modified surface 120.

[0034] The non-porous composite particles of the present disclosure are generally spherical. The diameter of the non-porous composite particles of the present disclosure is typically in the range of 1 micron to 14 microns, more typically in the range of 1 micron to 6 microns. The particle diameter is measured herein by dispersing the sample in methanol containing 5% lithium chloride using a Coulter counter (Beckman Coulter, Multisizer 4e Coulter Counter, Brea, CA, USA). For each sample, a count of more than 70,000 particles was run using a 30 μm hole in volume mode. Using the Coulter principle, the volume of the particle is converted into a diameter, wherein the particle diameter is an equivalent spherical diameter, and the equivalent spherical diameter is the diameter of a sphere having the same volume as the volume of the particle. The particle diameter is measured as the 50% cumulative diameter of the particle size distribution based on volume.

[0035] In some embodiments, the nonporous composite particles of the present disclosure have good stability even at pH greater than 12 and less than 1. For example, in embodiments, the nonporous composite particles according to the present technology exhibit less than 4% weight loss after exposure to an aqueous solution at a pH of 12.3 for 12 hours. Columns filled with these nonporous composite particles and exposed to alkaline conditions show minimal loss of separation performance. Therefore, the nonporous composite particles of the present disclosure having a nonporous polymer core and a nonporous inorganic-organic hybrid material are tailored to provide excellent separation of large biomolecules.

[0036] The nonporous composite particles of the present disclosure are also generally narrowly distributed in size. As defined herein, a collection of particles is "narrowly distributed in size" when the ratio of the 90% cumulative volume diameter divided by the 10% cumulative volume diameter is less than 1.4 when measured with a Beckman Coulter, Multisizer 4e Coulter Counter.

[0037] Nonporous polymer core

[0038] refer to Figure 1 The core 110 of the non-porous composite particle 100 is polymeric and non-porous. The polymer particle core used in the present disclosure comprises at least one organic polymer. The organic polymer core typically contains greater than 95% organic polymer, more typically greater than 97.5% organic polymer, and even more typically greater than 99% organic polymer.

[0039] The polymer particle core is non-porous, which is defined herein to mean that the polymer particle core has a pore volume of less than 0.1 cc / g. Preferably, in some embodiments, the organic polymer core has a pore volume of less than 0.10 cc / g (e.g., 0.05 cc / g), preferably less than 0.02 cc / g. The pore volume is determined based on a multi-point nitrogen adsorption experiment (Micromeritics ASAP 2400; Micromeritics Instruments Inc., Norcross, GA) using methods known in the art.

[0040] The diameter of the polymer core is typically in the range of, for example, 1 micron to 10 microns, more typically 1 micron to 5 microns. The polymer core is generally of narrow size distribution.

[0041] Basically, the polymer particle cores for use in the present disclosure include those composed of carbon and hydrogen, those composed of carbon, hydrogen and oxygen, those composed of carbon, hydrogen and nitrogen, and those composed of carbon, hydrogen, nitrogen and oxygen. The backbone of the organic polymer chain forming the polymer core may contain CC, CO, CN and / or ON covalent bonds. In some embodiments (e.g., in the case of polymers formed by free radical polymerization of vinyl groups), the backbone of at least one organic polymer chain may contain only CC covalent bonds.

[0042] As mentioned above, the polymer core for the present disclosure comprises at least one organic polymer. The at least one organic polymer comprises the residues of one or more organic monomers. The one or more organic monomer residues forming the at least one organic polymer may be selected from the residues of hydrophobic organic monomers, the residues of hydrophilic organic monomers, or a mixture of the residues of hydrophobic organic monomers and the residues of hydrophilic organic monomers.

[0043] The hydrophobic organic monomer may be selected from, for example, C2-C18 olefin monomers and / or monomers including C6-C18 monocyclic or polycyclic carbocyclic groups (e.g., phenyl groups, phenylene groups, naphthalene groups, etc.). Specific examples of hydrophobic organic monomers include, for example, monofunctional and polyfunctional aromatic monomers such as styrene, alkyl-substituted styrene, halogen-substituted styrene, divinylbenzene, and vinylbenzyl chloride; monofunctional and polyfunctional olefin monomers such as ethylene, propylene, or butylene; monofunctional and polyfunctional fluorinated monomers such as vinyl fluoride, 1,1-(difluoroethylene), tetrafluoroethylene, trifluorochloroethylene, hexafluoropropylene, perfluoropropyl vinyl ether, or perfluoromethyl vinyl ether; monomers having higher alkyl or carbon atoms; Monofunctional or multifunctional acrylate monomers having a cyclic group, for example, a monofunctional or multifunctional acrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group; monofunctional or multifunctional methacrylate monomers having a higher alkyl or carbocyclic group, for example, a monofunctional or multifunctional methacrylate monomer having a C6-C18 alkyl, alkenyl or alkynyl group or a C6-C18 saturated, unsaturated or aromatic carbocyclic group, and the like.

[0044] The hydrophilic organic monomer can be selected from, for example, a monofunctional or multifunctional organic monomer having an amide group, a monofunctional or multifunctional organic monomer having an ester group, a monofunctional or multifunctional organic monomer having a carbonate group, a monofunctional or multifunctional organic monomer having a carbamate group, a monofunctional or multifunctional organic monomer having a urea group, a monofunctional or multifunctional organic monomer having a hydroxyl group, and a monofunctional or multifunctional organic monomer having a nitrogen-containing heterocyclic group, etc. Specific examples of the hydrophilic organic monomer include, for example, vinyl pyridine, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl caprolactam, lower alkyl acrylates (e.g., methyl acrylate, ethyl acrylate, etc.), lower alkyl methacrylates (e.g., methyl methacrylate, ethyl methacrylate, etc.), vinyl acetate, acrylamide or methacrylamide monomers, hydroxypolyethoxy allyl ether monomers, ethoxyethyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, methylenebisacrylamide, allyl methacrylate, or diallyl maleate.

[0045] In various embodiments, the nonporous polymer core includes residues of a multifunctional hydrophobic organic monomer such as divinylbenzene and / or a multifunctional hydrophilic organic monomer such as ethylene glycol dimethacrylate, methylenebisacrylamide, or allyl methacrylate to provide crosslinking in the organic copolymer. In certain embodiments, DVB 80 may be employed, which is an organic monomer mixture comprising divinylbenzene (80%) and a mixture of ethyl-styrene isomers, diethylbenzene, and may also include other isomers.

[0046] In various embodiments, the polymer core may include only residues of multifunctional organic monomers. In various embodiments, the polymer may include residues of both multifunctional organic monomers and monofunctional organic monomers.

[0047] The present inventors have discovered that in some embodiments, the porosity of a material formed from a polymer containing multifunctional organic monomer residues can be reduced by adding monofunctional organic monomer residues to the polymer, or the porosity of a material formed from a polymer containing multifunctional organic monomer residues and monofunctional organic monomer residues can be reduced by increasing the amount of monofunctional organic monomer residues relative to the multifunctional organic monomer residues in the polymer. For example, it has been found that a polymer particle core formed from DVB 80 (which is formed from an organic polymer containing 80% multifunctional divinylbenzene monomer residues and monofunctional ethylstyrene monomer residues, as described above) has a porosity of about 0.015 cc / g, while an organic polymer core formed from DVB 80 and styrene (which contains multifunctional divinylbenzene monomer residues, monofunctional ethylstyrene monomer residues, and additional monofunctional styrene monomer residues) has a porosity of less than 0.007 cc / g.

[0048] In some embodiments, a polymer particle core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is formed by an organic homopolymer containing only a multifunctional organic monomer residue. In some embodiments, an organic polymer core is produced, wherein the central region of the core is formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, and the outer region of the core is also formed by an organic copolymer containing a multifunctional organic monomer residue and a monofunctional organic monomer residue, but wherein the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is increased relative to the central core region. In a specific example, an organic polymer core is produced, wherein the central region of the core is formed by DVB and styrene, and the outer region of the core is formed by DVB. In other embodiments, relative to the central core region, the molar ratio of the multifunctional organic monomer residue in the outer core region to the monofunctional organic monomer residue is reduced.

[0049] In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of a multifunctional organic monomer but not residues of a monofunctional organic monomer. In various embodiments, the entire polymer particle core may be formed from an organic polymer comprising residues of both multifunctional organic monomers and monofunctional organic monomers.

[0050] The polymer forming the polymer particle core can be prepared by a variety of methods and mechanisms, including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In a particularly advantageous embodiment, the nonporous polymer particle core is prepared via free radical polymerization.

[0051] In some embodiments, the polymer particle core of the present disclosure can be prepared by a dispersion polymerization method, in which a homogeneous solution is formed, wherein monomers, initiators, and stabilizers are combined in a solvent or solvent mixture. As the polymerization proceeds, the initially formed polymer precipitates out of the homogeneous solution to form precipitated nuclei. The formed precipitated nuclei still carry reactive sites, such as free radicals, which allow them to keep growing by continuously capturing and incorporating monomers and / or oligomers from the solution.

[0052] In an exemplary method based on free radical polymerization, one or more solvents and one or more stabilizers are purged with nitrogen to remove dissolved oxygen. Then, one or more monomers (including at least one multifunctional monomer) and a free radical polymerization initiator are added. Usually, under stirring, free radical polymerization is initiated by increasing the temperature for several hours. Based on the desired particle diameter, additional free radical polymerization initiators and additional monomers can be added to the reaction mixture to allow the particles to further grow to the desired size. After the reaction, the particles can be thoroughly washed and dried under vacuum.

[0053] Any free radical initiator compatible with the organic phase can be used alone or in a mixture of such free radical initiators. In a specific embodiment, the free radical initiator can be thermally activated or photoactivated. In a specific embodiment, the free radical initiator is a peroxide, peracetic acid, persulfate, azo initiator or a mixture thereof.

[0054] In the case where the initiator is a thermal initiator, the resulting solution can then be heated to an elevated temperature with stirring to activate the thermal initiator and maintained at the elevated temperature until polymerization is complete. In the case where the initiator is a photoinitiator, the resulting solution can then be irradiated with light of a suitable wavelength with stirring to activate the photoinitiator and maintained until polymerization is complete. Suitable organic monomers for the organic phase are as described above.

[0055] Solvent systems used to form polymer particle cores include methanol, ethanol, isopropanol, 2-methoxyethanol, water, acetonitrile, p-xylene, and toluene.

[0056] Stabilizers that can be used to form the polymer particle core include, for example, polyvinyl pyrrolidone (PVP); nonionic surfactants, including alkylphenol ethoxylates (e.g., Triton™ N-57, available from Dow Chemical); polyvinyl alcohol (PVA), such as Selvol TMPolyvinyl alcohol solution (available from Sekisui Special Chemicals); modified celluloses, including alkyl-modified celluloses such as methyl cellulose (e.g. Methocel TM , available from DuPont); and a hydrophobically modified cellulose hydroxyethyl cellulose stabilizer, such as Natrosol TM cetyl modified hydroxyethyl cellulose (available from Ashland); and ionic surfactants, including sodium alkyl sulfates, such as sodium dodecyl sulfate (SDS) and sodium oleyl sulfate, and the like.

[0057] In a specific embodiment of the nonporous polymer particle core formation, the monomers are a combination of DVB and styrene, the initiator is 2,2'-azobis(2-methylpropionitrile) (AIBN), the solvent system is a combination of reagent alcohol and p-xylene, and the stabilizer is polyvinylpyrrolidone (PVP 40).

[0058] Once formed, the organic polymer core may contain surface moieties from which further polymerization may be carried out. For example, nonporous polymer particle cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, or acryloxy moieties, etc.) from which further core growth may be carried out. Such further polymerization may be used to increase the size of a given batch of polymer particle cores by adding additional thickness of nonporous organic polymer to previously formed nonporous polymer particle cores.

[0059] In a specific embodiment of nonporous polymer particle core growth, the monomer is DVB, the solvent is reagent alcohol, and the stabilizer is polyvinylpyrrolidone (PVP 40).

[0060] Surface modified nonporous polymer core

[0061] In some embodiments, the present application is directed to nonporous polymer particles having a modified surface. That is, the nonporous polymer core 110 includes a modified surface 120 on the exterior of the core. (See Figure 1 ). In some embodiments, the modified surface of the nonporous polymer particles can form a covalent bond or an electrostatic bond with the subsequently applied nonporous organic-inorganic hybrid material 130. In certain embodiments, the modified surface of the nonporous polymer core is a silyl-modified surface. The silyl-modified surface can include a first functional group and a second functional group. For example, the first functional group is a reactive silane (e.g., an alkoxy group), and the second functional group is an organic polymerizable group (e.g., a vinyl group). The modified surface 120 can be used to connect or adhere the organic-inorganic hybrid nonporous material 130 to the core 110.

[0062] In some embodiments, the modified surface of the nonporous polymer particle core may have a thickness in the range of 1 nm to 300 nm, for example, any thickness in the range of 1 nm to 3 nm to 10 nm to 30 nm to 100 nm to 300 nm (i.e., in the range between any two of the foregoing values). In embodiments, the modified surface has a thickness of 10 nm to 30 nm or is defined by an area having about this thickness. That is, the thickness of the modified surface may extend only from the outer surface of the core; or in some embodiments, the thickness of the modified surface may extend into the core, because the outer portion of the core may be modified to define all or part of the thickness of the modified surface.

[0063] In some embodiments, the modified surface includes a surface polymer, which may include a surface polymer covalently or electrostatically bonded to an organic-inorganic hybrid nonporous material (e.g., Figure 1 The functional group of the material 130) of the electrostatically bonded organic-inorganic hybrid nonporous material includes an amide functional group and an amine functional group. In this regard, the organic-inorganic hybrid material described herein is weakly acidic in nature and therefore tends to be deprotonated and negatively charged, while the amide functional group or amine functional group described herein is basic in nature and therefore tends to be protonated and positively charged. Examples of functional groups covalently bonded to the organic-inorganic hybrid nonporous material include organosilane functional groups and organometallic functional groups, such as organotitanium functional groups and organozirconium functional groups. As used herein, an organosilane functional group is a functional group having at least one Si-C bond. Similarly, an organotitanium functional group is a functional group having at least one Ti-C bond, and an organozirconium functional group is a functional group having at least one Zr-C bond.

[0064] In some embodiments, the modified surface includes a surface polymer that may include monomer residues covalently or electrostatically bonded to an organic-inorganic hybrid nonporous material. Examples of monomer residues electrostatically bonded to an organic-inorganic hybrid nonporous material include amide monomer residues and amine monomer residues. Examples of monomer residues covalently bonded to an organic-inorganic hybrid nonporous material include organosilane monomer residues, organotitanium monomer residues, and organozirconium monomer residues. As used herein, an organosilane monomer residue is a monomer residue having at least one Si—C bond, an organotitanium monomer residue is a monomer residue having at least one Ti—C bond, and an organozirconium monomer residue is a monomer residue having at least one Zr—C bond.

[0065] The surface polymer may include, for example, polymer chains grafted onto a nonporous polymer core.

[0066] The surface polymer may include, for example, a cross-linked polymer network formed on a non-porous polymer particle core.

[0067] The surface polymers can be prepared by many methods and mechanisms, including, but not limited to, chain addition and stepwise condensation methods, free radical, anionic, cationic, ring opening, group transfer, metathesis, and photochemical mechanisms. In particularly advantageous embodiments, the nonporous polymer core is prepared via free radical polymerization.

[0068] As mentioned above, the polymer particle core may contain surface moieties from which further polymerization may be carried out. For example, organic polymer cores formed by free radical polymerization typically contain residual free radical polymerizable unsaturated surface moieties (e.g., ethylenyl moieties, vinyl moieties, methacryloxy moieties, acryloxy moieties, etc.) from which polymerization of surface polymers may be carried out. The polymer chains may be derived from monofunctional monomers. The crosslinked polymer network may be formed from multifunctional monomers. In addition to multifunctional monomers, monofunctional monomers may also be included in such crosslinked polymer networks.

[0069] As described above, surface polymers include those comprising amide monomer residues. Examples of amide monomer residues include amide monomer residues having the formula: wherein n is an integer from 1 to 3 (i.e., N-vinylpyrrolidone, N-vinyl-2-piperidone, or N-vinylcaprolactam). Examples of amide monomer residues also include those having the formula An amide monomer residue, wherein R1 is selected from C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene, and wherein R2 is selected from H, C1-C6 alkylene, C2-C6 alkenylene, C2-C6 alkynylene, C6-C18 arylene.

[0070] As also described above, surface polymers include those comprising amine monomer residues. Examples of amine monomer residues include aminoalkyl acrylates, aminoalkyl methacrylates, dialkylaminoalkyl acrylates, or dialkylaminoalkyl methacrylates, including amino-C1-C4-alkyl acrylates, amino-C1-C4-alkyl methacrylates, di-C1-C4-alkylamino-C1-C4-alkyl acrylates, di-C1-C4-alkylamino-C1-C4-alkyl methacrylates, such as 2-aminoethyl acrylate, 2-aminoethyl methacrylate, 2-(N,N-dimethylamino)ethyl acrylate, 2-(N,N-dimethylamino)ethyl methacrylate, 2-(N,N-diethylamino)ethyl methacrylate, or 2-diisopropylaminoethyl methacrylate.

[0071] As further described above, examples of surface polymers also include those comprising silane monomer residues electrostatically bonded to the organic-inorganic hybrid nonporous material. In some embodiments, the surface polymer comprises residues of one or more free radically polymerizable organosilane monomers.

[0072] Specific examples of free radical polymerizable organosilane monomers include unsaturated organosilane monomers (e.g., unsaturated organoalkoxysilane monomers, unsaturated organochlorosilane monomers, etc.), such as alkenyl or alkynyl functionalized organosilane monomers (e.g., alkenyl or alkynyl functionalized organoalkoxysilane monomers, alkenyl or alkynyl functionalized organochlorosilane monomers, etc.). Specific alkenyl functionalized organoalkoxysilane monomers include those having vinyl groups, methacryloxy groups, and acryloxy groups. Specific examples include 3-(trimethoxysilyl)propyl methacrylate (also known as 3-methacryloxypropyltrimethoxysilane or MAPTMOS), methacryloxypropyltriethoxysilane, methacryloxypropyltrichlorosilane, vinyltriethoxysilane (VTES), vinyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, (3-acryloxypropyl)trimethoxysilane, O-(methacryloxyethyl)-N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, -(triethoxysilylpropyl)urethane, N-(3-methacryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropylmethyldimethoxysilane, methacryloxypropyltri(methoxyethoxy)silane, 3-(N-phenylvinylmethyl-2-aminoethylamino)propyltrimethoxysilane hydrochloride, etc.

[0073] In a specific embodiment of the method for forming a surface-modified nonporous organic polymer core, an organosilane polymer, specifically a poly(styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane), is formed by copolymerizing a styryl-C1-C4-alkyl-tri-C1-C4-alkoxysilane monomer (wherein R is a C1-C4 alkyl) with a residual vinyl group (e.g., a residue of divinylbenzene) on the nonporous organic polymer core. Examples of styryl organosilane monomers include styrylethyltrimethoxysilane and styryltrimethoxysilane.

[0074] Organic-inorganic hybrid nonporous materials

[0075] As previously mentioned, the present disclosure relates to nonporous composite particles in which an organic-inorganic hybrid nonporous material is disposed on a surface-modified nonporous polymer core. Figure 1 As shown, the organic-inorganic hybrid nonporous material 130 forms and extends around the exterior of the particle 100 to create a layer. The modified surface 120 connects the material 130 to the core 110.

[0076] In some embodiments, the nonporous organic-inorganic hybrid material may have a thickness in the range of, for example, 1 nm to 4 microns, typically 25 nm to 200 nm. In some embodiments, the nonporous organic-inorganic hybrid material may have a pore volume of, for example, less than 0.1 cc / g (e.g., 0.05 cc / g), typically less than 0.02 cc / g.

[0077] "Organic-inorganic hybrid" materials include inorganic-based structures in which organic functional groups are integrated with both the internal or "framework" inorganic structure and the surface of the hybrid material. The inorganic portion of the hybrid material can be, for example, silicon dioxide, aluminum oxide, titanium, cerium or zirconium or their oxides, or a ceramic material. Exemplary hybrid materials are shown in U.S. Patents 4,017,528, 6,528,167, 6,686,035, 7,175,913 and 7,919,177, the disclosures of which are hereby incorporated in their entirety.

[0078] In some embodiments, the organic-inorganic hybrid nonporous material may include a silicon-based organic-inorganic hybrid material, which includes a hybrid region, wherein the silicon-based organic-inorganic hybrid material includes a silicon atom having one or more silicon-oxygen bonds and one or more silicon-carbon bonds. In some cases, the hybrid region may include a substituted or unsubstituted alkylene, alkenylene, alkynylene or arylene moiety bridging two or more silicon atoms. For example, the hybrid region may include a substituted or unsubstituted C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene moiety bridging two or more silicon atoms. In some embodiments, the hybrid region may include a substituted or unsubstituted C1-C6 alkylene moiety bridging two or more silicon atoms, including a methylene, dimethylene or trimethylene moiety bridging two silicon atoms. In some embodiments, the hybrid region may include a ≡Si-(CH2)n-Si≡ portion, where n is an integer and may be equal to 1, 2, 3, 4 or greater. In some embodiments, the nonporous organic-inorganic hybrid layer may include a silicon-based organic-inorganic hybrid material that includes an inorganic region in which the material includes silicon atoms having four silicon-oxygen bonds in addition to a hybrid region in which the material includes silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.

[0079] In various embodiments, the organic-inorganic hybrid material can be formed by hydrolytic condensation of one or more organosilane compounds on a surface modified nonporous organic polymer core such as those described above. As used herein, an organosilane compound is a silane compound having at least one Si-C bond.

[0080] The organosilane compound may include, for example, (a) one or more organosilane compounds of the formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, wherein at least one of Z1, Z2, Z3 and Z4 is C1-C4 alkyl, examples of which include alkyl-trialkoxysilanes, such as C1-C4-alkyl-tri-C1-C4-alkoxysilanes, including methyltriethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane or ethyltriethoxysilane, and dialkyl-dialkoxysilanes, such as C1-C4-dialkyl-di-C1-C4-alkoxysilanes, such as dimethyldiethoxysilane, dimethyldimethoxysilane, diethyldimethoxysilane or diethyldiethoxysilane. and many other possibilities, and / or (b) one or more organosilane compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6, wherein Z1, Z2 and Z3 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z1, Z2 and Z3 can be C1-C4 alkyl, wherein Z4, Z5 and Z6 are independently selected from Cl, Br, I, C1-C4 alkoxy, C1-C4 alkylamino and C1-C4 alkyl, but at most two of Z4, Z5 and Z6 can be C1-C4 alkyl, and wherein R is an organic group, for example selected from C1-C18 alkylene, C2-C18 alkenylene, C2-C18 alkynylene or C6-C18 arylene, typically C1-C4 alkylene, typically C1-C6 alkylene. Examples of compounds of the formula Z1Z2Z3Si—R—SiZ4Z5Z6 include bis(trialkoxysilyl)alkanes, for example, bis(tri-C1-C4-alkoxysilyl)C1-C4-alkanes such as bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane and bis(triethoxysilyl)ethane as well as many other possibilities.

[0081] In some embodiments, one or more additional non-organosilane compounds can be hydrolyzed and condensed with one or more organosilane compounds. Such compounds include silane compounds of formula SiZ1Z2Z3Z4, wherein Z1, Z2, Z3 and Z4 are independently selected from Cl, Br, I, C1-C4 alkoxy and C1-C4 alkylamino. In certain embodiments, the additional silane compound is tetra-C1-C4-alkoxysilane, such as tetramethoxysilane or tetraethoxysilane.

[0082] In some embodiments, the organic-inorganic hybrid material can be formed by hydrolytic condensation of the following substances on the surface-modified nonporous organic polymer core as described above: (a) one or more alkoxysilanes, such as tetraalkoxysilanes (e.g., tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), etc.), and (b) one or more organosilanes, for example, selected from bis(trialkoxysilyl)alkanes (e.g., bis(trimethoxysilyl)methane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane (BTEE), etc.) and / or alkyltrialkoxysilanes (e.g., methyltrimethoxysilane, methyltriethoxysilane (MTOS), ethyltriethoxysilane, etc.). In the case where the plurality of silane compounds includes one or more bis(trialkoxysilyl)alkanes, an alkyl-bridged organic-inorganic hybrid material is prepared, which can provide various advantages over conventional silica-based materials, including chemical and mechanical stability. When BTEE is used as a monomer, the resulting material is an ethylene bridged hybrid (BEH) material. A specific BEH material can be formed by the hydrolytic condensation of TEOS and BTEE.

[0083] In some embodiments, a plurality of silane compounds as described above (e.g., a plurality of silane compounds comprising one or more organosilanes and one or more tetraalkoxysilanes) are partially condensed to form a polyalkoxyorganosiloxane oligomer, which is then hydrolyzed and condensed onto the surface-modified nonporous organic polymer core. For example, BTEE and TEOS may be partially condensed to form a polyethoxyorganosiloxane oligomer (PEOS), which is hydrolyzed and condensed onto the surface-modified nonporous organic polymer core.

[0084] In various embodiments, the organic-inorganic hybrid nonporous material can be formed by producing (usually in a series of steps) a reaction mixture comprising the following components: a surface-modified nonporous organic polymer core, ethanol, one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)), water, and a basic or acidic catalyst, the catalyst being used to promote the hydrolysis and condensation of the silanes of the organic-inorganic hybrid material on the surface-modified nonporous organic polymer core. In some embodiments, the hydrolysis is carried out at room temperature. In some embodiments, the mixture can be heated to drive the hydrolysis reaction to completion. In some embodiments, the mixture is stirred. After the organic-inorganic hybrid nonporous material is formed, the resulting particles can be washed and dried.

[0085] In other embodiments, organic-inorganic hybrid nonporous materials can be formed by the interaction between a template surfactant (e.g., and an ionic surfactant such as hexadecyltrimethylammonium bromide (CTAB) or trioctylmethylammonium bromide (TOMB)) and one or more silanes (including one or more organosilanes as described above (e.g., TEOS and BTEE, or PEOS)) during the continuous addition of silanes, alkaline catalysts, and template surfactants to a surface-modified nonporous organic polymer core. The process results in continuous silane hydrolysis and condensation of organic-inorganic hybrid reaction products on the core. The reaction can be carried out at room temperature or elevated temperature.

[0086] One or more organosilanes (e.g., TEOS and BTEE, or PEOS) as described above can be hydrolyzed in the presence of a surface-modified nonporous (NP) organic polymer core having a surface polymer comprising monomer residues of an amide monomer and / or a silane monomer, such that the hydrolyzed organosilane forms an organic-inorganic hybrid nonporous layer or region on the core.

[0087] Potential advantages of the disclosed nonporous composite particles include improved mass transfer and increased efficiency relative to nonporous silica particles, and increased pH stability. The nonporous composite particles can be used as chromatographic packing materials for separation of small molecules and large biologics.

[0088] Chromatographic device

[0089] In some aspects of the present disclosure, the non-porous composite particles described herein can be provided in a suitable chromatographic device. For this reason, the non-porous composite particles described herein can be provided together with a suitable housing. The non-porous composite particles and the housing can be supplied independently, or the non-porous composite particles can be pre-packaged in the housing. The housing used according to the present disclosure generally includes a chamber for receiving and holding non-porous composite particles. In various embodiments, the housing can be provided with an inlet and an outlet leading to the chamber and leading out from the chamber.

[0090] Suitable materials of construction for the chromatography housing include inorganic materials, for example, metals such as stainless steel and ceramics such as glass, and synthetic polymeric materials such as polyethylene, polypropylene, polyetheretherketone (PEEK), and polytetrafluoroethylene, among others.

[0091] In certain embodiments, the chromatography housing may include one or more filters for retaining the non-porous composite particles in the housing. Exemplary filters may be in the form of, for example, a membrane, a mesh, a frit, or a spherical porous filter.

[0092] In certain embodiments, the chromatographic device is a chromatographic column.

[0093] The present disclosure also provides a kit comprising a nonporous composite particle, a housing or a device as described herein, and instructions for use. In one embodiment, the instructions are for a separation device, such as a chromatography column.

[0094] Chromatographic separation

[0095] In some aspects of the present disclosure, the non-porous composite particles of the present disclosure can be used for a variety of chromatographic separation methods. Therefore, chromatographic devices and chromatographic suits described herein can also be used for such methods. The example of the chromatographic separation method of the non-porous composite particles of the present invention can be used includes being used for high pressure liquid chromatography (HPLC) and ultra-high pressure liquid chromatography (UHPLC) in different modes. Those modes include but are not limited to affinity separation, hydrophilic interaction chromatography (HILIC) separation, normal phase separation, reversed phase separation, chiral separation, supercritical fluid chromatography SFC separation, perfusion separation, size exclusion chromatography (SEC) separation, ion exchange separation or multi-mode separation.

[0096] The non-porous composite particles, devices and kits disclosed herein can be used for chromatographic separation of substances such as small molecules, carbohydrates, antibodies, whole proteins, peptides and / or DNA.

[0097] Such chromatographic separations may include loading a sample onto the non-porous composite particles according to the present disclosure, and eluting the adsorbed species from the non-porous composite particles with a mobile phase.

[0098] Such chromatographic separations can be performed in conjunction with a variety of aqueous and / or organic mobile phases (i.e., in mobile phases containing water, organic solvents, or a combination of water and organic solvents) and in conjunction with a variety of mobile phase gradients (including gradients of solvent type, temperature, pH, salt concentration, or other parameters).

[0099] The following examples are provided to illustrate how to make composite particles and components thereof according to the present technology. These examples are for illustrative purposes only and should not be considered restrictive. When an amount, concentration or other value or parameter is given as a list of ranges, preferred ranges or upper preferred values ​​and lower preferred values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether the range is disclosed separately. In the case of numerical ranges listed herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within the range. When limiting the range, the scope of the present technology is not intended to be limited to the specific value described.

[0100] Example 1: Non-porous poly(DVB80) particle core

[0101] In this example, an exemplary nonporous core was fabricated. Other methods and other materials may be utilized to fabricate the nonporous polymer core of the composite particles of the present technology.

[0102] The inhibitors in divinylbenzene (80%, technical grade) used in the particle synthesis were removed by passing the monomer through an alumina filter cartridge.

[0103] Primary particle synthesis: In this particle synthesis experiment (Sample 1A in Table 1 below), 65.1 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirring device, a condenser and a thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile and 105 grams of divinylbenzene were charged to the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours. Primary nucleus growth: When the 20 hour reaction time was reached, the temperature was maintained at 70°C and 1.8 grams of azobisisobutyronitrile was added. Subsequently, a solution of 67.6 g of divinylbenzene and 20.3 g of PVP-40 in 202.7 g of reagent alcohol was metered in via a pump at a constant flow rate over 120 minutes. The reaction was continued at 70° C. for at least 12 hours. After the reaction, the particles were separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone in sequence. The final product was placed in a vacuum oven and dried overnight at 45° C. Approximately 147 g of 1.95 μm particles were obtained.

[0104] To test the effect of adjusting the amount of PVP-40 at the start of the reaction, three different amounts were evaluated (65.1 g - Sample 1A; 48.9 g - Sample 1B; and 109.2 g - Sample 1C). The results are provided in Table 1 below, which show that particle size is inversely correlated with the amount of PVP-40.

[0105]

[0106] Table 1

[0107] Example 2: Nonporous Poly(DVB80-co-styrene) Particle Core

[0108] In this example, an exemplary non-porous core was fabricated that included a polymer core comprising two different polymers. Other methods and other materials may be utilized to fabricate the non-porous polymer core of the composite particles of the present technology.

[0109] The inhibitors in divinylbenzene (80%, technical grade) and styrene used in the particle synthesis were removed by passing the monomers through an alumina filter cartridge.

[0110] Primary Particle Synthesis: In this particle synthesis experiment (Sample 2A), 78.2 grams of PVP-40, 8.9 grams of Triton N-57, 2452.6 grams of reagent alcohol (905 ethanol, 5% methanol and 5% isopropanol) and 153.3 grams of p-xylene were charged into a 4L round bottom flask reactor equipped with a mechanical stirrer, condenser and thermocouple. The mixture was stirred and mixed at 200 RPM, and the dissolved oxygen in the solution was removed by subsurface purging with nitrogen. After the dissolved oxygen was below 1 ppm, 2.1 grams of azobisisobutyronitrile, 42 grams of divinylbenzene (80%, technical grade) and 63.0 grams of styrene were charged to the reaction. The reaction temperature was raised to 70°C and maintained at this temperature for 20 hours.

[0111] Primary nucleus growth: When a reaction time of 20 hours is reached, the temperature is maintained at 70°C and 1.8 g of azobisisobutyronitrile is added. Subsequently, a solution of 67.6 g of divinylbenzene and 19.2 g of PVP-40 in 192.0 g of reagent alcohol is metered in via a pump at a constant flow rate over 120 minutes. The reaction is continued at 70°C for at least 12 hours. After the reaction, the particles are separated from the reaction slurry by filtration and subsequently washed with methanol, tetrahydrofuran (THF) and acetone in sequence. The final product is placed in a vacuum oven and dried overnight at 45°C. Approximately 135 g of 2.2 μm particles are obtained.

[0112] In Table 2 below, samples 2A to 2C describe the synthesis of poly(DVB80-co-styrene) particles having different compositions of DVB80 and styrene by adjusting the amounts of DVB80 and styrene charged in the primary nucleus synthesis step of the nucleus growth step. The particle size distribution of the poly(DVB80-co-styrene) of sample 2C is described in Figure 2 , and a microscopic image of the particles is depicted in Figure 3 middle.

[0113]

[0114] Table 2

[0115] Example 3: A larger particle core made from another smaller core

[0116] In this example, an exemplary nonporous core was fabricated that included a core fabricated in two stages.Other methods and other materials may be utilized to fabricate the nonporous polymer core of the composite particles of the present technology.

[0117] 120 grams of particles (particle size, 2.32 μm) prepared by the method described in Sample 2D were redispersed in a solution containing 37.0 grams of PVP-40, 4.5 grams of Triton™ N-57, 100.0 grams of p-xylene, and 1234.0 grams of reagent alcohol (90% ethanol, about 5% methanol, and about 5% isopropanol) and then loaded into a 4-liter kettle reactor equipped with a mechanical stirring device, a condenser reactor, and a thermocouple. The slurry was mixed at 200 RPM and nitrogen was purged through the surface to obtain dissolved oxygen below 1 ppm. Once the dissolved oxygen in the solution was below 1 ppm, the nitrogen subsurface sparge was changed to a blanket sparge, the stirring speed was adjusted to 75 RPM, and the reaction temperature was then increased to 70°C. When the reaction temperature reached 70°C, 4.8 grams of divinylbenzene (80%, de-inhibited with alumina) and 3.0 grams of AIBN were added. After 15 minutes, a solution containing 139.5 g of divinylbenzene (80%, with alumina to remove inhibitors), 105.6 g of PVP-40 and 1345.7 g of reagent alcohol was added by a pump at a constant rate over 2 hours. After addition, the reaction was maintained at 70°C for 20 hours. After the reaction, the particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally with acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 250 g of monodisperse 3.0 μm particles were obtained.

[0118] Example 4: Core surface primer with silane functional groups

[0119] In this example, an exemplary primed nonporous core was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core of the composite particles of the present technology.

[0120] The inhibitors in divinylbenzene (80%, technical grade) and styrylethyltrimethoxysilane were removed by passing through an alumina filter cartridge. The reagent alcohol used in the reaction contained 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment (see sample 4A in Table 3 below), 44.7 grams of PVP-40 and 165.2 grams of p-xylene were loaded into a 4L round-bottom flask reactor equipped with a mechanical stirring device, a condenser reactor and a thermocouple. A slurry of 145.0 grams of particles (sample 1A, from Example 1) in 1490.7 grams of reagent alcohol was added. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution was less than 1ppm, the reaction mixture was heated to 70°C and the stirring speed was adjusted to 75RPM. Then, 2.9 grams of divinylbenzene and 2.5 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 14.5 grams of styrylethyltrimethoxysilane, 1.5 grams of divinylbenzene and 13.9 grams of PVP-40 in 464.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 149.0 grams of primed particles were obtained.

[0121] Table 3 provides the synthesis of primer particles with different surface morphologies and primer thicknesses by adjusting the amount of primer monomer and the amount of crosslinker DVB80 used in a number of different samples. Figures 4 to 9 Primed particles with different surface morphologies and primer thicknesses according to the following samples are shown. Figure 4 and Figure 5 Primed particles of Sample 4G are depicted. Figure 6 and Figure 7 Primed particles of sample 4H are depicted. Figure 8 and Fig. 9 Primed particles of Sample 4I are depicted.

[0122]

[0123] Table 3

[0124] Example 5: Core surface primer with other functional groups

[0125] In this example, exemplary primed nonporous cores with various functional groups were fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer cores of the composite particles of the present technology.

[0126] Here, with reference to sample 5A (as shown below), the primer monomer of the primer-free polymer core is replaced. Specifically, the reagent alcohol used in the reaction contains 90% ethanol, about 5% methanol and about 5% isopropanol. In this particle synthesis experiment, 15.4 grams of PVP-40 and 57.0 grams of p-xylene are loaded into a 1L round-bottom flask reactor equipped with a mechanical stirring device, a condenser, a reactor and a thermocouple. Add 50.0 grams of a slurry of particles made in Example 3 in 514.0 grams of reagent alcohol. The mixture was mixed at 200RPM for 24 hours. The reaction slurry was then purged subsurface with nitrogen to obtain dissolved oxygen below 1ppm. Once the dissolved oxygen in the solution is less than 1ppm, the reaction mixture is heated to 70°C and the stirring speed is adjusted to 75RPM. Then, 1.8 grams of divinylbenzene and 0.9 grams of 2,2'-azobis(2-methylpropionitrile) (AIBN) were added. After mixing for 15 minutes, a solution containing 9.0 grams of N-vinyl pyrrolidone, 0.9 grams of divinyl benzene and 3.6 grams of PVP-40 in 120.0 grams of reagent alcohol was added at a constant flow rate over 2 hours. After the reaction was maintained at 70°C for a total of 20 hours, the reaction was cooled to below 40°C and the resulting particles were separated from the reaction slurry by filtration. The particles were then washed with methanol, followed by tetrahydrofuran (THF) and finally acetone. The final product was placed in a vacuum oven and dried overnight at 45°C. 54.0 grams of primed particles were obtained.

[0127] Samples 5A to 5E, shown below, describe the synthesis of primed particles with different surface functional groups. In each sample, the primer monomer was replaced in the formulation of the primed nonporous polymer core. While the above experiments utilized sample 5A, additional experiments were performed utilizing samples 5B to 5E. Fig.10 and Fig.11 depicts the particles before priming, and Fig.12 and Fig.13 Depicted is the process of coating the particles with poly(N-vinylpyrrolidone) Figure 5 and Figure 6 Changes in particle shape.

[0128]

[0129] Example 6: Nonporous Hybrid Coating on Trimethoxysilane Primer Core

[0130] In this example, an exemplary primed nonporous core with a hybrid coating was fabricated to form a nonporous composite particle according to the present technology.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.

[0131] In this particle synthesis experiment (i.e., for Sample 6A), a 5 L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor, and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 140.0 grams of silane primed cores (Sample 4A) were redispersed in 1120.0 grams of 200 proof ethanol and then loaded into the reactor. 1120.0 grams of toluene and 26.9 grams of Pluronic F127 and 77.1 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The temperature of the ultrasonic bath was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the temperature of the ultrasonic bath reached 35°C, a solution containing 98.2 g of tetraethyl orthosilicate (TEOS), 41.8 g of 1,2-bis(triethoxysilyl)ethane (BTEE), and 3.5 g of Pluronic F127 in a mixed solvent of 70.0 g of ethanol (200 proof) and 70.0 g of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was maintained at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was placed in a vacuum oven and dried overnight at 70°C. 174.0 g of non-porous BEH coated particles (i.e., sample 4A particles coated with non-porous BEH material) were obtained.

[0132] Table 4 below provides the synthesis of nonporous hybrid coated particles (Samples 6A-6H) with different coating thicknesses and surface morphologies by adjusting the amounts of TEOS, BTEE and with or without the use of surfactant. Fig.14 and Fig.15 Non-porous hybrid coated particles of samples 6D and 6H are depicted, respectively, showing hybrid coated particles with different coating thicknesses and surface morphologies.

[0133]

[0134] Table 4

[0135] Example 7. Nonporous Hybrid Coating on Pyrrolidone Primed Core

[0136] In this example, an exemplary primed (primed with pyrrolidone) nonporous core with a hybrid coating was fabricated.Other methods and other materials may be utilized to fabricate the primed nonporous polymer core with a hybrid coating of the composite particles of the present technology.

[0137] A 5L round bottom flask reactor equipped with a mechanical stirring device, condenser, reactor and thermocouple was set up in an ultrasonic bath capable of heating (490 watts). 14.0 grams of pyrrolidone primed cores (Sample 5A) were redispersed in 112.0 grams of 200 proof ethanol and then loaded into the reactor. 112.0 grams of toluene, 2.7 grams of Pluronic F127 and 7.7 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C for ultrasonic treatment. The ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 9.8 grams of tetraethyl orthosilicate (TEOS), 4.2 grams of 1,2-bis(triethoxysilyl)ethane (BTEE), 0.4 grams of Pluronic F127 in a mixed solvent of 7.0 grams of ethanol (200 proof) and 7.0 grams of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was kept at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70°C overnight. 16.0 g of non-porous BEH coated particles were obtained.

[0138] Example 8. Nonporous hybrid coating with high organic composition

[0139] In this example, a nonporous hybrid coating with a high organic content is produced, and a material layer is formed around the primer nonporous polymer core. Other methods and other materials can be used to produce nonporous coatings of composite particles of the present technology.

[0140] A 3L round-bottom flask reactor equipped with a mechanical stirring device, a condenser and a thermocouple was placed in an ultrasonic bath capable of heating (490 watts). 75.0 grams of silane-primed core material (sample 4D, Example 4) was redispersed in 75.0 grams of 200 standard ethanol and then loaded into the reactor. 750.0 grams of toluene and 79.7 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 42.3 grams of tetraethyl orthosilicate (TEOS) and 107 grams of 1,2-bis(triethoxysilyl)ethane (BTEE) in a mixed solvent of 241.7 grams of ethanol (200 standard) and 241.7 grams of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was kept at 35°C for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70° C. overnight. 110.0 g of coated particles were obtained.

[0141] Example 9: Nonporous hybrid coating with a mixture of methylene and ethylene bridged organosilanes

[0142] In this example, another nonporous hybrid coating is produced and a material layer is formed around the primer nonporous polymer core. Other methods and other materials can be used to produce nonporous coatings of composite particles of the present technology.

[0143] A 1L round-bottom flask reactor equipped with a mechanical stirrer, condenser and thermocouple was placed in an ultrasonic bath capable of heating (490 watts). 18.0 grams of silane-primed cores were redispersed in 144.0 grams of 200-proof ethanol and then loaded into the reactor. 144.0 grams of toluene and 10.5 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 71.4 grams of bis(triethoxysilyl)methane, 18.6 grams of 1,2-bis(triethoxysilyl)ethane (BTEE) in a mixed solvent of 90.0 grams of ethanol (200 standard) and 90.0 grams of toluene was metered into the reactor at a constant flow rate over 6 hours. After addition, the reaction was kept at 35°C for 24 hours. The coated particles were separated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70°C overnight.

[0144] Example 10: Nonporous hybrid coating with gradient inorganic / organic ratio

[0145] In this example, a nonporous hybrid coating having a variation in inorganic / organic ratio over at least a portion of its thickness is fabricated and a layer is formed around a primed nonporous polymer core.Other methods and other materials may be utilized to fabricate nonporous coatings of composite particles of the present technology.

[0146] A 1L round-bottom flask reactor equipped with a mechanical stirring device, a condenser and a thermocouple was placed in an ultrasonic bath capable of heating (490 watts). 18.0 grams of silane-primed core material (Sample 4F, Example 4) was redispersed in 144.0 grams of 200-proof ethanol and then loaded into the reactor. 144.0 grams of toluene and 10.5 grams of ammonium hydroxide (28%-30% aqueous solution) were added to the slurry in the reactor. The ultrasonic bath temperature was raised to 35°C and ultrasonic treatment was started. Ultrasonic treatment was maintained throughout the coating process. When the ultrasonic bath temperature reached 35°C, a solution containing 27.5 grams of tetraethyl orthosilicate (TEOS) and 7.5 grams of 1,2-bis(triethoxysilyl)ethane (BTEE) in a mixed solvent of 45.0 grams of ethanol (200 standard) and 45.0 grams of toluene was metered into the reactor at a constant flow rate over 4 hours. After two hours, solution A and solution B containing 40 g of 1,2-bis(triethoxysilyl)ethane (BTEE) in a mixed solvent of 45.0 g of ethanol (200 proof) and 45.0 g of toluene were metered into the reactor at a constant flow rate over 4 hours. After both solution A and solution B were completed, the reaction was maintained at 35° C. for 24 hours. The coated particles were isolated by filtration and washed 6 times with methanol. The final product was dried in a vacuum oven at 70° C. overnight.

Claims

1. A non-porous composite particle, comprising: a nonporous polymer particle core having a silyl-modified surface; as well as A nonporous organic-inorganic hybrid layer is in contact with the silyl-modified surface.

2. The particle of claim 1, wherein the non-porous polymer particle core is the product of at least one monomer.

3. The particle of claim 2, wherein the at least one monomer is a free radical polymerizable monomer.

4. The particle of claim 2, wherein the at least one monomer comprises at least two functional groups.

5. The particle of claim 2, wherein the at least one monomer is capable of being polymerized by ring-opening polymerization or polycondensation.

6. The particle of claim 1 wherein the nonporous polymer particle core comprises divinylbenzene (80%).

7. The particle of claim 1, wherein the silyl-modified surface of the nonporous polymer particle core comprises a first functional group and a second functional group, the first functional group comprising a reactive silane and the second functional group comprising an organic polymerizable group. The particle of claim 7 , wherein the reactive silane comprises an alkoxy group.

9. The particle of claim 7, wherein the organic polymerizable group comprises a vinyl group.

10. The particle of claim 1, wherein the silyl-modified surface of the nonporous polymer particle is modified with at least one of N-vinylpyrrolidone, N-vinylcaprolactam, N,N-dimethylvinylbenzylamine, methacryloxypropyltrimethoxysilane, or p-phenylvinyltrimethoxysilane.

11. The particle of claim 1 wherein the silyl-modified surface of the nonporous polymer particle core comprises at least one functional group covalently bonded to an organometallic compound.

12. The particle of claim 1, wherein the silyl-modified surface of the nonporous polymer particle core comprises at least one functional group that electrostatically interacts with the nonporous organic-inorganic hybrid layer.

13. The particle according to claim 1, wherein the nonporous organic-inorganic hybrid layer has a thickness ranging from 1 nm to 4 micrometers, more preferably from 25 nm to 200 nm.

14. The particle of claim 1, wherein the nonporous organic-inorganic hybrid layer has a pore volume of less than 0.10 cc / g.

15. The particle of claim 1, wherein the nonporous organic-inorganic hybrid layer comprises a material selected from the group consisting of silica, alumina, titanium, cerium, zirconium, silicon dioxide, alumina, ceria, zirconium oxide, ceramic materials, and combinations thereof.

16. The particle of claim 1, wherein the nonporous organic-inorganic hybrid layer comprises a silicon-based material.

17. The particle of claim 16, wherein the silicon-based material comprises silicon atoms having one or more silicon-oxygen bonds and one or more silicon-carbon bonds.

18. The particle of claim 16, wherein the nonporous organic-inorganic hybrid layer comprises substituted or unsubstituted alkylene, alkenylene, alkynylene, or arylene moieties bridging two or more silicon atoms.

Citation Information

Patent Citations

  • Preparation of organically modified silicon dioxides

    US4017528A

  • Porous hybrid particles with organic groups removed from the surface

    US6528167B2

  • Porous inorganic / organic hybrid particles for chromatographic separations and process for their preparation

    US6686035B2

  • Porous hybrid particles with organic groups removed from the surface

    US7175913B2

  • Porous inorganic / organic hybrid particles for chromatographic separations and process for their preparation

    US7919177B2